Learning and Memory - From Molecules and Cells to Mind and Behavior 2022
DOI: 10.5772/intechopen.108244
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Imagery and Emotional Control

Abstract: Olfaction and gustation are important survival mechanisms. These sensory modalities also have an impact on memory and emotions. Olfactory stimulation has recently been used in virtual reality environments to treat emotional distress. There is evidence that olfactory and gustatory stimuli reach the insula, where they influence a number of other brain networks. There is little research on the use of smell and taste during mindfulness, but it will be shown that they can foster balanced emotional responses. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[85] Recent studies have also demonstrated that olfactory stimulation can lead to CS. [86,87] However, the speci c mechanisms in humans need to be elucidated further. [86,88] It should be noted that cells with germline mutations may not necessarily transform into cells of origin for gliomas.…”
Section: Genomic Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[85] Recent studies have also demonstrated that olfactory stimulation can lead to CS. [86,87] However, the speci c mechanisms in humans need to be elucidated further. [86,88] It should be noted that cells with germline mutations may not necessarily transform into cells of origin for gliomas.…”
Section: Genomic Instabilitymentioning
confidence: 99%
“…[ 85 ] Recent studies have also demonstrated that olfactory stimulation can lead to CS. [ 86 , 87 ] However, the specific mechanisms in humans need to be elucidated further. [ 86 , 88 ]…”
Section: Mechanisms Linking Chronic Stress To the Hallmarks Of Gliomamentioning
confidence: 99%